2015
DOI: 10.1149/2.0601504jes
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization and Electrocatalytic Activity of Poly(4-thienylacetyl-amino-2,2,6,6-tetramethylpiperidinyl-1-yloxy)/(2,2′-bithiophene) Copolymer

Abstract: Monomer 4-thienylacetyl-amino-2,2,6,6-tetramethylpiperidinyl-1-yloxy (TATEMPO) has been synthesized. The homopolymer poly(2,2 -bithiophene) (PBTh), and poly(4-thienylacetyl-amino-2,2,6,6-tetramethylpiperidinyl-1-yloxy)/(2,2 -bithiophene) (PTATEMPO/BTh) copolymer are successfully prepared on platinum in boron trifluoride diethyl etherate solution by electrochemical polymerization. They are characterized by scanning electron microscopy. The electrochemical copolymerization of TATEMPO and BTh may be accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…One feasible way to synthesize polythiophene-organic radical polymers is through FeCl 3 -aided oxidative polymerization; however, polymerization is uncontrolled, and the products are intractable, preventing solution processing and characterization. 31 Electropolymerization of thiophene monomers bearing pendant nitroxide radicals has been reported; 33,48,49 however, only one type of such polymer was reported due to the limited commercial availability of monomers. The physical properties of polythiophene-organic radical polymers is even less well understood and remains an intriguing topic.…”
mentioning
confidence: 99%
“…One feasible way to synthesize polythiophene-organic radical polymers is through FeCl 3 -aided oxidative polymerization; however, polymerization is uncontrolled, and the products are intractable, preventing solution processing and characterization. 31 Electropolymerization of thiophene monomers bearing pendant nitroxide radicals has been reported; 33,48,49 however, only one type of such polymer was reported due to the limited commercial availability of monomers. The physical properties of polythiophene-organic radical polymers is even less well understood and remains an intriguing topic.…”
mentioning
confidence: 99%
“…The band at 1176 cm −1 was related to C-H in-plane bending of 2,6-lutidinium cation [58,59]. It confirmed that 2,6-lutidine got a hydrogen proton to become 2,6-lutidinium cation during the electrocatalytic process [60,61]. Meanwhile, three negative-going bands at 1685, 1360, and 1267 cm −1 were detected, which were attributed to C=O stretching vibration, C-H deformation vibration in the methyl group, and skeleton vibration of acetophenone, respectively [62].…”
Section: Resultsmentioning
confidence: 95%
“…BTh is the dimer of the thiophene unit that can be easily electropolymerized by potentiostatic, galvanostatic, or potentiodynamic techniques . Even if potential sweep techniques require longer reaction times to obtain well-attached polymer films compared to potentiostatic or galvanostatic measurements, this method is used due to the possibility to monitor the electrochemical properties of the growing polymer, along the polymerization process, allowing a detailed study of the electropolymerization kinetics. Hence, the electropolymerization of the monomer was carried out potentiodynamically by repetitive cycling of the electrode potential (between 0.0 and 1.2 V vs Ag/AgCl) in a solution containing 9.8 mM of the monomer and 0.1 M LiClO 4 in ACN:water (1:1 v/v), at a scan rate of 50 mV·s –1 (see SI, Figure S11). Under these conditions, an irreversible oxidation process on the surface of the ITO electrode in the ACN:water system was observed, showing in the first potentiodynamic cycle the typical trace-crossing effect observed during the electrochemical polymerization of π-conjugated systems .…”
Section: Resultsmentioning
confidence: 99%